Antara Sabâiyah dan Ghulat: Menakar Ekstremitas Sekte-sekte Shiâah Melalui Konsep ImÃ¢mah - Umam, Fawaizul (ISLAMICA: Jurnal Studi Keislaman, 2008)
Extremist discourse is found within the Shiâite community just as it is also found within the Sunnite group. Within the former, the existence of the sectarian groups âit may be argued- serves as the raison dâÄtre of extremism. These groups emerged first and foremost as a result of the diverging and somewhat conflicting views on the notion of ImÄmah; a notion that always forms part and parcel of the Shiâi tenet. This is in addition to the fact that they emerge as a logical result of the doctrinal disparity that members of these group hold on various issues. It is out of these differences however, that the modulation of Shiâism into the moderates and the extremists -that is the right and the misled Shiâism as it were- comes into being. What this implies is that that kind of modulation is not simply about the classification and social identification of Shiâism. It is also about the categorical stigmatization of members of the group toward each other. Hence, the competing truth-claim among them ends up in a seemingly endless political conflict. In this, those who are judged misled such as the Shiâah Sabâiyah, are often called the âghulatâ. Nonetheless, some scholars argue that the identification of this group as âghulatâ is not due to its misleading tenet, but because of its doctrinal extremism. The more extreme a group becomes, the more misled it is. To me however, this later view is problematic simply because there is no a standardized measure of who is misled and who is not. Vis-Ã -vis this problem, this paper is destined to investigate the epistemological significance of the word âmisleadingâ that the Shiâah Sabâiyah is associated with, and is also interested to find out to what extent this group may be rightly called extremist. All this will be done through the serious study on the central tenet of Shiâism, namely imÄmah.